Pesantren Multikultural: Alternatif Pendidikan di Era Milenial - Akramun Nisa Harisah (IAIN Sorong, 2018)
The track record of the schools showed that schools have a role and contribute to the social dynamics it means that life need change. Related to social change, the Indonesian people are faced with multicultural discourse , the emergence of nuanced conflicts and acts of racial violence in the name of religion by a religious group , at least it shows that the Indonesian people are religious diversity has not been able to resolve with the other in a conducive and constructive environment. Religion in relation to multicultural education indicates a doctrine of relationship between Islam as a religion with education and also to multiculturalism. The essence of multicultural schools is the students will foster cultural sensitivity pluralistic society, and emphasized a caring attitude and are willing to accept the difference or the politics of recognition, that means recognition of the existence of people from minority groups in every way in order to reach unity in diversity, without reducing the original ethnicity as students.